Magnetospheric Multiscale Observation of an Electron Diffusion Region at High Latitudes. Issue 15 (3rd August 2020) - Burkholder, B. L.; Nykyri, K.; Ma, X.; Rice, R.; Fuselier, S. A.; Trattner, K. J.; Pritchard, K. R.; Burch, J. L.; Petrinec, S. M.
Abstract: On 17 October 2016, Magnetospheric Multiscale (MMS) sampled an electron diffusion region (EDR) embedded in an electron‐scale current sheet within a mixed portion of the high‐latitude magnetosheath adjacent to the magnetopause. We analyze the generalized Ohm's law, dissipation, and electron velocity distributions inside the EDR. The velocities, magnetic fields, and densities observed in the magnetosheath and magnetosphere indicate the magnetopause was unstable to the Kelvin‐Helmholtz instability, which can form electron‐scale current sheets. Alternatively, a current sheet was observed in the solar wind at L1 40 min before the MMS observations, which could have been compressed by the bow shock initiating reconnection. Hundreds of keV particles near the EDR may have been locally accelerated. Plain Language Summary: We present observations of an electron diffusion region (EDR) that was observed well removed from the geomagnetic equator. The EDR is a small volume of the plasma where nonideal physics breaks down and particle acceleration occurs. Magnetic field energy is dissipated as kinetic energy of the plasma, having large‐scale consequences in the plasma even though the conversion occurs on extremely small scales. Access to such small scales has only recently been made possible with the high temporal resolution of instruments on board the Magnetospheric Multiscale spacecraft. Key Points: Observations occur in the dusk sector near the high‐altitude southern geomagnetic cusp Parallel electric fields and crescent‐shaped electron distributions indicate MMS crosses through an electron diffusion region The observed electron diffusion region occurs at an electron‐scale current sheet near the magnetopause